Successful management of daytime enuresis using alarm procedures: a randomly controlled trial. Issue 2 (February 1987) - Halliday, S; Meadow, S R; Berg, I
Abstract : Forty four children with daytime wetting were included in a randomly controlled trial of two alarm devices, a contingent one that sounded when wetting occurred and a non-contingent one that went off from time to time unrelated to wetting events. A quota allocation system ensured comparability between treatment groups. Two thirds responded to an alarm by becoming dry. The non-contingent alarm produced as good a response as the contingent one and is recommended for routine use in children with diurnal enuresis. Twenty three per cent of those who responded to treatment relapsed up to two years after completion of the trial.